Analisis Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan CV. Lembaga Palembang - Fatma Oktarendah; Metha Aditya Putri (Penerbit Goodwood, 2023)
Purpose: This study aims to determine and evaluate the performance of employees at CV. Lembaga located in Palembang, South Sumatra. Methodology: During the research process and data collection, it was carried out using a questionnaire which was distributed to 22 respondents, who were employees of CV. Lembaga itself. By using descriptive analysis method. Questionnaires were analyzed with multiple linear regression analysis. Results: The results showed that the work environment has a partial and significant positive effect on performance and work motivation has a positive and significant effect on performance. Simultaneously the work environment and work motivation have a positive and significant effect on performance. Limitations: Unreturned questionnaires, limited scope of research area, and limited variable became the limitations of this study. Contributions: Hopefully for future researchers to convey the variables of job satisfaction, leadership style and work stress.